Overcoming obstacles to innovation: Can an educated workforce help? - Benoît Dostie; Lene Kromann; Anders Sørensen (Journal of Innovation & Knowledge (JIK), 2025)
Firms face many obstacles in their pursuit of innovation. However, the mechanisms that enable firms to surmount these challenges and foster innovation are less understood. This study thus investigates whether the better performance of firms with higher human capital is due to their increased ability to overcome obstacles to innovation. Our estimation strategy accounts for the fact that facing obstacles is endogenous by correcting for the sample selection bias that is involved in determining which firms face obstacles. It appropriately estimates the impact of firms' skill intensity on their propensity to innovate under two sets of circumstances - facing obstacles or not. Using a combination of rich survey and register data from over 2000 Danish firms for the period of 2006 to 2018, we also address several other biases that could affect our estimation of the impact of skill intensity on overcoming obstacles. Our results provide strong evidence that firms facing challenges in their innovation process are more likely to succeed when they have higher skill intensity. This applies to large and small firms as well as to firms in the service and manufacturing sectors, and it applies regardless of the type of innovation and, to some extent, which obstacles they face. Interestingly, we find that increasing skill intensity has no impact on the likelihood of innovation for firms that do not face obstacles. In contrast, firms that face obstacles can increase their likelihood of innovation by up to 25 %-points through higher skill intensity.
Keywords: C18; D22; O03; 650; Innovation; Obstacles; Education; Workforce; Endogenous switching regression model